The Effect of Storage Conditions on the Potency of Newcastle Disease Vaccine La Sota - Okwor, E.C.; Eze, D.C.; Uzuegbu, M.O. (International Journal of Poultry Science, 2009)
Thirty (30) vials of Newcastle Disease (ND) vaccine. La Sota were procured locally and tested for potency when stored under conditions of irregular power supply. The vaccines were of the same batch and were eighteen months to the expiration time. The potency of the vaccines was tested using Haemagglutination (HA) test before storage. The vaccines’ immunogenicity was determined in a batch of 250, 3 weeks old white cockerels after which the vaccines were stored in the refrigerator with two-third of the storage period at 0-4oC and the remaining one third at room temperature of 26-30oC. During the study, the methods of vaccine storage were alternated frequently to reflect the frequent power outages. The humoral immune response of the vaccinated chickens was estimated by Haemagglutination Inhibition (HI) test. The potency of the vaccines was tested on days 28, 56, 84, 112 and 140 post storage. On day 140, another batch of 250, 3 weeks old white cockerels were vaccinated with a vial from the stock and the humoral immune response of these chickens was evaluated at 3 weeks post vaccination. The mean HA titre of the vaccine before storage was 128, while the mean HA titres of the vaccines after storage (i.e., day 140) was 8. The mean HI titres of the vaccinated chickens before and after storage were 1005.7 and 8.3, respectively. Student t test was used to compare the mean HI titre of the chicken vaccinated prior and at the end of vaccine storage. The GMT mean HI titre of the chickens vaccinated prior to storage was significantly (p<0.05) higher than that of the chicken vaccinated at the end of vaccine storage.